Mechanical thrombectomy for anterior circulation stroke: 5-year experience in a statewide service with differences in pretreatment time metrics across two hospitals sites. (9th May 2016) - Kabra, Ruchi; Phillips, Timothy J; Saw, Jacqui-Lyn; Phatouros, Constantine C; Singh, Tejinder P; Hankey, Graeme J; Blacker, David; Ghia, Darshan; Prentice, David; McAuliffe, William
Abstract : Objective: To audit our institutional mechanical thrombectomy (MT) outcomes for acute anterior circulation stroke and examine the influence of workflow time metrics on patient outcomes. Methods: A database of 100 MT cases was maintained throughout May 2010—February 2015 as part of a statewide service provided across two tertiary hospitals (H1 and H2). Patient demographics, stroke and procedural details, blinded angiographic outcomes, and 90-day modified Rankin Scale (mRS) scores were recorded. The following time points in stroke treatment were recorded: stroke onset, hospital presentation, CT imaging, arteriotomy, and recanalization. Statistical analysis of outcomes, predictors of outcome, and differences between the hospitals was carried out. Results: Thrombolysis in Cerebral Infarction (TICI) 2b/3 reperfusion was 79%. Forty-nine per cent of patients had good clinical outcomes (mRS 0–2). In a subgroup analysis of 76 patients with premorbid mRS 0–1 and first CT performed ≤4.5 h after stroke onset, 60% had good clinical outcomes. Patient and disease characteristics were matched between the two hospitals. H1 had shorter times between hospital presentation and CT (32 vs 55 min, p=0.01), CT and arteriotomy (33 vs 69 min, p=0.00), and stroke onset and recanalization (198 vs 260 min, p=0.00). These time metrics independently predicted good clinical outcome. Median days spent at home in the first 90 days was greater at H1 (61 vs 8, p=0.04) than at H2. A greater proportion of patients treated at H1 were independent (mRS 0–2) at 90 days (54% vs 42%); however, this was not statistically significant (p=0.22). Conclusions: Outcomes similar to randomized controlled trials are attainable in 'real-world' settings. Workflow time metrics were independent predictors of clinical outcome, and differed between the two hospitals owing to site-specific organizational differences.